Clinical phenotype and outcome of hepatitis E virus-associated neuralgic amyotrophy - van Eijk, Jeroen J J; Dalton, Harry R; Ripellino, Paolo; Madden, Richard G; Jones, Catherine; Fritz, Miriam; Gobbi, Claudio; Melli, Giorgia; Pasi, Emanuela; Herrod, Jenny; Lissmann, Rebecca F; Ashraf, Hamad H; et al. (Neurology, 2017)
To determine the clinical phenotype and outcome in hepatitis E virus-associated neuralgic amyotrophy (HEV-NA). Cases of NA were identified in 11 centers from 7 European countries, with retrospective analysis of demographics, clinical/laboratory findings, and treatment and outcome. Cases of HEV-NA were compared with NA cases without evidence of HEV infection. Fifty-seven cases of HEV-NA and 61 NA cases without HEV were studied. Fifty-six of 57 HEV-NA cases were anti-HEV IgM positive; 53/57 were IgG positive. In 38 cases, HEV RNA was recovered from the serum and in 1 from the CSF (all genotype 3). Fifty-one of 57 HEV-NA cases were anicteric; median alanine aminotransferase 259 IU/L (range 12-2,961 IU/L); in 6 cases, liver function tests were normal. HEV-NA cases were more likely to have bilateral involvement (80.0% vs 8.6%, < 0.001), damage outside the brachial plexus (58.5% vs 10.5%, < 0.01), including phrenic nerve and lumbosacral plexus injury (25.0% vs 3.5%, = 0.01, and 26.4% vs 7.0%, = 0.001), reduced reflexes ( = 0.03), sensory symptoms ( = 0.04) with more extensive damage to the brachial plexus. There was no difference in outcome between the 2 groups at 12 months. Patients with HEV-NA are usually anicteric and have a distinct clinical phenotype, with predominately bilateral asymmetrical involvement of, and more extensive damage to, the brachial plexus. Involvement outside the brachial plexus is more common in HEV-NA. The relationship between HEV and NA is likely to be causal, but is easily overlooked. Patients presenting with NA should be tested for HEV, irrespective of liver function test results. Prospective treatment/outcome studies of HEV-NA are warranted.